Zamba and Formelehre: a Formal Approach of the Zamba in Dialogue with Some Recent Trends in Music Theory (Revista Argentina de Musicología, 2016)
In this paper we study the formal organization in the zamba genre, using a formal-functional approach as presented by William Caplin and other authors. We present a modular formal-functional model of the zamba also inspired by James Hepokoski and Warren Darcy’s Sonata Theory. We analyze and discuse several musical examples that show various intra-thematic formal alternatives of the zamba. Finally, the first stanza of two well known zambas, Debajo de la morera and Zamba del riego are analyzed in detail, incorporating the prolongational graphs proposed by Lerdahl and Jackendoff.
Keywords: zamba; music analysis; formal function; modular-form; Wiliam Caplin